Selective Catalytic Reduction of NOx with NH3 over Mn2O3 Supported with Different Morphology of CeO2 Catalysts - Sunder Rao S.; Kumar Patel V.; Sharma S. (My University, 2025)
Three different morphologies of CeO2 supports (nanoparticle, nanocube, and nanorod) were prepared by hydrothermal technique and further Mn2O3 metal was impregnated on CeO2 supports using wet-impregnation methods, and their activity for NO reduction using NH3−SCR technique was analysed. The synthesized catalysts and supports were further characterized through scanning electron microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS), and transmission electron microscopy (TEM), and Brunauer-Emmett-Teller (BET). The catalytic performance of Mn2O3/CeO2-nanoparticle has shown the highest conversion (76 %) compared to the other two catalysts in the temperature range of 50–450 °C. © 2022 Wiley-VCH GmbH.